The Effect of folding booklet education on the level of knowledge of family caregivers of stroke patients - Nur Rohmah, Anis Ika; Husna, Layyinatul; Al Husna, Chairul Huda; Purwanto, Edi; Handayani, Tri Lestari (University of Muhammadiyah Malang, 2024)
Introduction: As many as 25 – 75% of stroke patients need the help of family caregivers to help with daily activities. Most family caregivers have insufficient knowledge and abilities, where family caregivers need support and education from nurses in providing education to family caregivers while they are still in the hospital. Objectives: Identifying the influence of folding booklet education on the level of knowledge of family caregivers of stroke patients at Wava Husada Kepanjen Hospital. Methods: The design used in this research was a quasi-experiment with the one group pre-test post-test design. The total sample of 30 family caregivers of stroke patients was taken using accidental sampling on February 6 - February 19 2023. The level of knowledge of family caregivers of stroke patients was measured using a stroke knowledge level questionnaire and provided education using a folding booklet. Results: The majority of respondents were aged 36-45 years (36.7%), female (70.0%), high school (50.0%), working (56.7%), no care experience (90.0%). Before being given foldlet (folding booklet) education, the majority of respondents had a good level of knowledge (43.3%), after being given foldlet (folding booklet) education, respondents with good knowledge increased (90.0%). Statistical test analysis obtained p value = 0.001 < 0.05. Conclusions: The majority of family caregivers before being given foldlet (folding booklet) education had a level of knowledge in the good category, likewise after being given foldlet (folding booklet) education the level of knowledge in the good category increased, so there was an influence of foldlet (folding booklet) education on the level of knowledge of family caregivers of stroke patients.